The action learning handbook : powerful techniques for education, professional development and training - McGill, Ian (RoutledgeFalmer, 2004)
Action learning is a continued process of learning and reflection with the support of a group of colleagues, working on real issues. The action learning method is increasingly used to bring innovation to many different fields of work. The principles of action learning can achieve improvement and transformation in a wide range of applications and disciplines, including professional training and educational contexts. This book is a comprehensive guide to action learning which maintains an accessible, practical focus throughout. It is packed with useful resources, including case studies and id.